Comparative study on the occurrence and incidence of insect pests due to climate change in coastal and haor rice ecosystem (Journal of the Asiatic Society of Bangladesh, Science, 2026)
The survey and assessment were carried out at three coastal and three haor districts of Bangladesh to know the occurrence and incidence of insect pests of rice due to climate change in coastal and haor rice ecosystem during June 2022 to July 2023. The infestations of insect pests in rice ecosystem are changing gradually with time due to changing in climate. Sixteen (16) insect pests of rice and six (6) natural enemies were recorded on rice field of coastal and haor ecosystem. Stem borer, rice leaf roller and Brown plant hopper were one of the major insect pests in coastal and haor rice ecosystems in survey areas. Among three coastal districts, the highest number of stem borer (4.5/30 hills) followed by leaf roller (4.4/30 hills) was observed on boro rice in Khulna followed by Noakhali and the lowest number in Bhola (3.4/30 hills) on T aman rice. Among three haor districts, the highest number of stem borer (3.4/30 hills) in Habigonj followed by Sunamgonj (3.1/30 hills) and the lowest number of stem borer in Kishoregonj (2.9/30 hills). In case of leaf roller, similar trend was also observed on boro rice. Major insect pests of rice is higher in boro season than those of  T aman season. Stem borer, rice leaf roller, rice bug and brown plant hopper were one of the major insect pests of rice in coastal and haor rice ecosystems in survey areas. The incidence of 4 major insect pest species of rice crop was higher in coastal rice ecosystem compared to haor rice ecosystem.J. Asiat. Soc. Bangladesh, Sci. 51(2): 165-175, December 2025